Place vs. Node transit: Planning policies revisited - Olaru, D.; Moncrieff, Simon; McCarney, G.; Sun, Y.; Reed, Tristan; Pattison, C.; Smith, B.; Biermann, S. (M D P I AG, 2019)
A core contemporary planning approach is the promotion of transit-oriented developments (TODs) and in recent times cities have committed substantial financial investment to encourage sustainable precincts around public transport. Evaluation of the success of TODs is key for continuing the planning efforts. A frequently applied framework for characterizing TODs draws on Bertolini's Node-Place (N-P) model, enriched through application in various contexts. We offer here an extension to the N-P model, using a case study in a low-density city, Perth,Western Australia. A typology of railway stations is developed using 43 indicators and then linear models are applied to ascertain the association between patronage and station precinct features. The results show that various types of measures are required to increase public transport ridership for the four clusters that emerged from the analysis. Density alone does not lead to increased use of public transport; it must be associated with city-wide accessibility, as well as access/egress to and from the station.